STUDENTS’ PERCEPTIONS OF THE INTEGRATION OF TRI HITA KARANA VALUES IN DESCRIPTIVE WRITING - Ni Made Wersi Murtini; I Made Sutajaya; I Wayan Suja (Jurnal Santiaji Pendidikan (JSP), 2025)
This study explored students’ perception toward the implementation of Tri Hita Karana (THK) in descriptive paragraph writing activity in English Language Education Study Program Unmas Denpasar. This qualitative study aims to find out students’ perception of the application of THK in descriptive writing class. This study employed qualitative method involving 30 students of English Language Education Study Program. The data were collected through semi-structure interview. The analysis was focused on related themes with the students’ perceptions of the integration of THK values in descriptive paragraph writing. The result of the research indicated that in general the students see it positively to the integration of THK with descriptive writing activity. They feel that the values of THK improved the quality of their descriptive writing by writing more meaningful content which is culturally more relevant. Students also noted that these values help them express their idea more creatively and deeply connected with the writing topic. This finding showed that integrating the values of local culture like THK in English learning could enhance students’ descriptive writing skill and culture understanding. This approach makes the students learning process more interesting and contextually meaningful for students.